The Empirical Research of Hawgent Dynamic Mathematics Technology Integrated into Teaching Fraction in Primary School - Tommy Tanu Wijaya; Zhou Ying; Aditya Purnama (Mathematics Education Study Program, 2020)
STEAM education that is under ICT has become an upsurge in the international education of research and practice. Due to this, there is a wide application of information technology that has a profound impact to mathematics education. Based on the multiple representation of mathematics, this research aims to test the effectiveness of Hawgent dynamic mathematic software in teaching mathematics to primary students. The sample of this study are all the primary students in Bandung and this research uses the test and non-test method. The test method is a quantitative test to know the students’ mathematical understanding ability when using Hawgent and traditional teaching method. The data collected from the test method would be the post-test scores and the scores are both from the experimental and controlled class. The data will then be process by using SPSS 22 and Microsoft Excel. The data is then analyzed by using the t-test statistic. The result of this study concludes that the students’ understanding ability whose learning are supported by Hawgent are better than whose learning are using the traditional teaching method.